2016
DOI: 10.1007/s00383-016-3990-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis: state of the art review

Abstract: Appendicitis is a common cause of abdominal pain in children. The diagnosis and treatment of the disease have undergone major changes in the past two decades, primarily as a result of the application of an evidence-based approach. Data from several randomized controlled trials, large database studies, and meta-analyses have fundamentally affected patient care. The best diagnostic approach is a standardized clinical pathway with a scoring system and selective imaging. Non-operative management of simple appendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 152 publications
3
90
1
10
Order By: Relevance
“…From the present study and other studies evaluating integration of US with PAS [20, 21], or with Alvarado score [20, 2224], and from recent guidelines on pediatric appendicitis [27, 28], it seems that patients should be categorized into three different groups based on the clinical prediction score: one group with low probability (0–3 points), one with intermediate probability (4–6 points), and one group with high probability of appendicitis (8–10 points). It seems that children in the low probability group could safely be sent home without US.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…From the present study and other studies evaluating integration of US with PAS [20, 21], or with Alvarado score [20, 2224], and from recent guidelines on pediatric appendicitis [27, 28], it seems that patients should be categorized into three different groups based on the clinical prediction score: one group with low probability (0–3 points), one with intermediate probability (4–6 points), and one group with high probability of appendicitis (8–10 points). It seems that children in the low probability group could safely be sent home without US.…”
Section: Discussionmentioning
confidence: 94%
“…Children in the high probability group may not benefit from an US since the rate of false-negative results seems to increase which may mislead the surgeon. Hence, in presence of a high clinical prediction, the physician has different options, where the two most accurate seem to be active observation or diagnostic laparoscopy according to the most recent published guidelines [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…However, for such a common disease, its etiology is not yet fully understood. Several hypotheses have been proposed, including luminal obstruction, infection, innate immunity, and adaptive immunity related to hygiene [3,4,5,6]. In the 1980s, Barker et al reported that improvement in household amenities and piped water supply was followed by an increased rate of acute appendicitis, suggesting a ‘hygiene hypothesis’ that reduced early exposure to gut pathogens in children possibly altered the adaptive immunity with inappropriate or excessive inflammatory response leading to appendicitis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Отдельные эндохирургические методики, прежде все-го, лапароскопическая аппендэктомия, получили широ-кое распространение в практике детской хирургии, дока-зали свою эффективность [4][5][6][7], однако даже в этом случае далеко не всеми авторами лапароскопическая аппендэктомия признается безусловным методом выбо-ра при лечении детей с деструктивным аппендицитом и аппендикулярным перитонитом [8].…”
unclassified
“…Наиболее разработаны алгоритмы ведения детей с острым аппендицитом [4,7,34]; А. Дроновым и соавт. [4] разработаны алгоритмы применения лапа-роскопии при большинстве экстренных состояний (таких как острый аппендицит, кишечная инвагинация, спаеч-ная болезнь, дивертикул Меккеля), предложена хирур-гическая тактика при ургентных заболеваниях органов малого таза у девочек, описан алгоритм эндоскопиче-ского и лапароскопического этапа при кишечной инва-гинации у детей.…”
unclassified